2021
DOI: 10.1128/mcb.00382-20
|View full text |Cite
|
Sign up to set email alerts
|

A Novel cis Regulatory Element Regulates Human XIST in a CTCF-Dependent Manner

Abstract: The long non-coding RNA XIST is the master regulator for the process of X chromosome inactivation (XCI) in mammalian females. Here we report the existence of a hitherto uncharacterized cis regulatory element (cRE) within the first exon of human XIST , which determines the transcriptional status of XIST during the initiation and maintenance phases of XCI. In the initiation phase, pluripotency factors bind to this cRE and keep XI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Then we extracted the SP1 binding sites of genes from RegNetwork database [ 30 ] and found that more than 43% (32/73) of EsP genes contain SP1 binding motifs around their promoter regions. SP1 can play parallel roles with YY1 and CTCF in regulating XIST transcription from the XIST promoter [ 31 ]. And the binding motif of SP1 was reported to be exclusively enriched in the regulatory elements on the Xa rather than Xi [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then we extracted the SP1 binding sites of genes from RegNetwork database [ 30 ] and found that more than 43% (32/73) of EsP genes contain SP1 binding motifs around their promoter regions. SP1 can play parallel roles with YY1 and CTCF in regulating XIST transcription from the XIST promoter [ 31 ]. And the binding motif of SP1 was reported to be exclusively enriched in the regulatory elements on the Xa rather than Xi [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%